Contributions of naturalistic parent-child conversations to children’s science learning during informal learning at an aquarium and at home - Ocular, Grace; Kelly, Kimberly R.; Millan, Lizbeth; Neves, Savannah; Avila, Kateri; Hsieh, Betina; Maloles, Claudine (Frontiers in Psychology, 2022)
This study examined the naturalistic conversations of 62 parent-child dyads during informal learning at an aquarium and with a subsample at home. Children (Mage = 69.8 months) with their parents were observed and audio recorded while exploring an aquarium exhibit, and a subset of dyads returned recorded home conversations reminiscing about the aquarium visit. Parent-child conversations at the aquarium were coded for child science talk and a range of parent talk variables, and parent-child conversations at home were coded for child science talk and talk about the value of the aquarium visit. Results revealed that parents tended to use more elaborative statements compared to other talk types in the aquarium. Yet, the different types of questions and statements that parents used with their children at the aquarium differentially related to their children’s science talk in the aquarium and while reminiscing at home. Findings highlight often-overlooked types of parent talk that provide meaningful ways for families to engage in science and may lead to positive child learning outcomes.